2021
DOI: 10.1186/s12883-021-02170-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of global distribution of multiple sclerosis: an ecological investigation based on Global Burden of Disease data

Abstract: Background Socioeconomic factors may be involved in risk of multiple sclerosis (MS), either indirectly or as confounding factors. In this study two comprehensive indicators reflecting socioeconomic differences, including the Human Development Index (HDI) and Prosperity Index (PI), were used to assess the impact of these factors on the worldwide distribution of MS. Methods The data for this global ecological study were obtained from three comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…24 This difference arises from discrepancies in the level of hygiene, urbanization, access to clean water, and various other socioeconomic factors. Regarding MS, contrastingly, countries with a higher human development index have a higher prevalence of MS. 25 At first glance, an inverse relationship between MS and H. pylori may be observed, but given the inconclusive results in subgroup analysis in our study, both in laboratory methods and in geographical areas, the need for more comprehensive studies is evident.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…24 This difference arises from discrepancies in the level of hygiene, urbanization, access to clean water, and various other socioeconomic factors. Regarding MS, contrastingly, countries with a higher human development index have a higher prevalence of MS. 25 At first glance, an inverse relationship between MS and H. pylori may be observed, but given the inconclusive results in subgroup analysis in our study, both in laboratory methods and in geographical areas, the need for more comprehensive studies is evident.…”
Section: Discussionmentioning
confidence: 59%
“…25 An investigation of GBD data revealed that the average prevalence of MS in developing and developed countries is 11.64 (95% CI, 9.65-13.63) and 51.21 (95% CI, 40.93-61.48) per 100,000 population, respectively, which increased with increasing national Human Development Index (HDI). 25 In this regard and according to "hygiene hypothesis," it is proposed that infections with pathogens, including H. pylori, in early childhood can reduce the risk of autoimmune diseases, such as MS. 26 In contrast, Kountouras et al 18 proposed that active H. pylori infection may have a contributing role in the pathogenesis of MS, and some evidence has suggested that H. pylori infection promotes autoimmune diseases, such as Guillain-Barré syndrome, autoimmune pancreatitis, and autoimmune-mediated mucosal atrophy. [27][28][29][30][31] These conflicting proposals continue to stimulate epidemiological studies examining the possible link between H. pylori infection and MS, 8,17 but, thus far, findings have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown significant increase in MS cases, both as a proportion of their populations (MS prevalence) and in terms of growing cases (MS incidence) across North America and several European countries (the United Kingdom, Germany, Denmark). Although Europe had the highest reported incidence at 6.8, followed by the Americas at 4.8, Canada showed the highest prevalence as a country, at 168 people per 100,000, and the highest incidence, at 5.63 per 100,000 ( 18 ), while the US almost doubled its prevalence (913,925 cases) from 2013 to 2019 ( 19 ). Moreover, increasing prevalence was also reported across the MENA region, in addition to the Russian Federation, and Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a greater burden of MS was reported in countries with high socio-economic status (20). This observation is supported by the high-risk of MS in Northern Europe and North America, where ≥100 cases are diagnosed per 100,000 population (20,21). A lower risk of MS is found in Africa and Asia, where the prevalence is <30 cases per 100,000 population (22)(23)(24).…”
Section: Introductionmentioning
confidence: 94%
“…About 2.8 million cases of MS were diagnosed worldwide in 2020 (7). Interestingly, a greater burden of MS was reported in countries with high socio-economic status (20). This observation is supported by the high-risk of MS in Northern Europe and North America, where ≥100 cases are diagnosed per 100,000 population (20,21).…”
Section: Introductionmentioning
confidence: 96%